Psychosocial rehabilitation experiences of women victims of armed conflict in Montes de María, Colombia - Laura Camila Sarmiento-Marulanda; Amira Ayleen Aguilera-Char; Catalina González-Gil; Wilson López-López (BMC, 2021)
Abstract Background After 9 years of the ground-breaking social policy Law 1448 of 2011 -Victims Law- and its extension until 2030, the Colombian State and other stakeholders have made several efforts towards granting the right of integral reparation for more than 9 million victims that are recognized in the Colombian transitional context. Psychosocial rehabilitation is a Victims Law's reparation measure whose objective is to re-establish the psychosocial, physical and mental health welfare in the individual, familiar and community levels. This study aims to understand the experiences of psychosocial rehabilitation of women victims of armed conflict in Montes de Maria and the underlying social intervention paradigms that guide the Law's implementation. Methods Based on a qualitative design with a phenomenological approach, narrative tools and thematic network analysis permitted to give voice to the women participants. Individual narrative interviews were conducted with 12 women victims and a focus group with eight of them was used as a triangulation strategy. Results Although the Victims Law is oriented by a sociopolitical intervention paradigm, the stories of the women's victims of Montes de María mainly evidenced non-sociopolitical interventions with humanitarian assistance towards revictimization and State abandonment. As a coping mechanism towards the State negligence encountered, women strive to overcome psychosocial trauma by developing agency and community resources for the resignification of the traumatic experiences and peacebuilding. Conclusions For the Victims Law to achieve its integrality aim, the psychosocial approach should be implemented through all its measures but remains absent in Montes de Maria. The diversity of victim's individual and collective initiatives that were found, can contribute towards transformative and participatory psychosocial intervention with community's resources. Women victims can perform as advisors and collaborators in the implementation of individual and collective reparation, which remains as an opportunity for psychosocial rehabilitation and peacebuilding. Further monitoring and evaluation of the law with a territorial and differential perspective is required to respond to the victim's needs.